Tata kelola perusahaan dan pengaruhnya terhadap struktur modal - Widijaya Widijaya; Peny Peny (Jurnal Ekonomi Modernisasi, 2020)
This research aims to determine the impact of board composition, ownership structure, and firm characteristics on the capital structure of non-financial companies listed on the Indonesia Stock Exchange. Board independence, Board size, audit committee, director tenure, ownership concentration, family ownership, and director ownership are used as independent variables in this study. Firm size, firm age, firm performance, firm risk, and agency costs are the control variables. Data were collected using the purposive sampling method with a total of 1,695 observational data that met the criteria for 5 years. The Panel regression method is used to analyze the impact of each independent variable on the dependent variable. The fixed-effects model is found to be the best regression model in this research. This study found that board size, director tenure, and family ownership had a significant negative impact on capital structure, while board independence, audit committee, ownership concentration, and director ownership did not impact significantly on capital structure. A larger board size forms strong corporate governance which leads to less risky capital structure decisions. Longer director tenure improves the decision quality of a capital structure, and family ownership helps to maintain firm value by ensuring capital structure decisions made are the best for the company. Ownership factors are encouraged in future studies such as foreign ownership, government ownership, and institutional ownership in examining the impact on capital structure.